Principals Going above and Beyond: Understanding Organizational Citizenship Behavior among School Principals. Issue 2 (March 2017) - Nutov, Liora; Somech, Anit
Organizational citizenship behavior (OCB) refers to all behaviors outside the formal role definition but which contribute to organizational functioning and performance. To date research has focused on teachers' OCB in an attempt to identify the causes and consequences of such behavior for the individual and the organization. Questions that have yet to be addressed in the literature are: Do principals also engage in OCB? And if so, how do they interpret OCB, and what are its characteristics? Since this is the first study to inquire into the phenomenon of OCB in the context of principalship, the qualitative method was chosen for the investigation. Fifteen post-elementary school principals were interviewed. Our findings identified four categories of principals' OCB: effort invested in the school community; initiatives; supporting the local community; and other exceptional behaviors. We conclude by delineating the findings' theoretical and practical implications and by introducing a proposed platform for new directions in OCB research.